Wishtree eaudiobook - Applegate, Katherine (Listening Library, 2017)
Trees can't tell jokes, but they can certainly tell stories. . . . Red is an oak tree who is many rings old. Red is the neighborhood "wishtree"―people write their wishes on pieces of cloth and tie them to Red's branches. Along with her crow friend Bongo and other animals who seek refuge in Red's hollows, this "wishtree" watches over the neighborhood. You might say Red has seen it all. Until a new family moves in. Not everyone is welcoming, and Red's experiences as a wishtree are more important than ever. Funny, deep, warm, and nuanced,  Wishtree  is Newbery Medalist and  New York Times –bestselling author Katherine Applegate at her very best―writing from the heart, and from a completely unexpected point of view.